Assessment of biorational insecticides and Beauveria bassiana (Vuill) for control of the tomato fruit budworm - García Gutiérrez, Cipriano; Armenta Bojórquez, A. Dagoberto; Gaxiola Castro, L. Alberto; Vázquez Montoya, Nadia; Acuña Jiménez, Monica (Agricultura, Sociedad y Desarrollo, 2020)
An experimental trial was carried out on tomato in Guasave, Sinaloa, to evaluate the effectivity of biorational insecticides Bacillus thuringiensis (Berliner) (Versa™), Pyrethrins (Abatec™), Sterneinema carpocapsae (Capsanem™) at commercial doses, and a native strain of Beauveria bassiana (Vuill) at a dose of 2.1x108 spores/ml, against larvae of the second instar of the fruit budworm, Heliothis virescens (Fabricius). The percentage of dead larvae (DL), the average of fruits damaged by the insect, and the tomato yield were evaluated in each treatment. The bacteria B. thuringiensis caused 39.6% of dead larvae, Pyrethrins 32.3% and S. carpocapsae 23.3%, while the native strain of B. bassiana only had 16% and the control 2.6%, 72 hours after having been applied. In the experiment, no statistical differences were found between bacteria and pyrethrins in fruits damaged, but they were found between the strains of B. bassiana. There were also no statistical differences between the yield obtained from tomatoes in the batches treated with bacteria, pyrethrins and nematodes (Tukey; p ≤ 0.05). These results indicated a higher effectiveness of biorational insecticides regarding the entomopathogenic fungus for control of the second instar larvae of H. virescens in tomato crop Type Roma used in the food industry in Sinaloa, Mexico.